PKM Literasi Keuangan Melalui Pelatihan Trading Saham Syariah Pada Guru-Guru MGMP Akuntansi dan Ekonomi SMA Se-Kota Pariaman - Erly Mulyani; Halkadri Fitra; Salma Taqwa; Henri Agustin; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2020)
This community service aims to increase partner literacy about Islamic stock trading. Partners in this service are MGMP accounting and economics teachers in SMA Pariaman City. This community service provides training, discussion, practice and monitoring to partners. There were 25 participants who took part in this activity. After the training, the participants were able to make transactions in the capital market. This can be seen from the activities of the participants who directly buy and sell Islamic shares using the POST PRO application.